O raciocínio geográfico e as chaves de leitura da Covid-19 no território brasileiro - Guimarães, Raul Borges [UNESP]; Catão, Rafael De Castro; Martinuci, Oséias Da Silva; Pugliesi, Edmur Azevedo [UNESP]; Matsumoto, Patricia Sayuri Silvestre (Instituto de Estudos Avançados da Universidade de São Paulo, 2020)
To understand how covid-19 is distributed in Brazil, geographers use geographical reasoning supported by mapping techniques and spatial representation. We thus propose here a series of procedures to understand the disease in the geographic space, first with an exploration and descriptive analysis of the data, a spatial analysis and a synthesis through graphical modeling, followed by a cartographic communication. As a result, we hope that this theoretical and methodological path may guide the creation of a world image capable of responding to the most urgent demands posed by the pandemic, and concomitantly create reflections on how the production of geographical space creates vulnerabilities in this perverse globalization.

Para compreender como a Covid-19 se distribui pelo espaço brasileiro, os geógrafos utilizam-se do raciocínio geográfico apoiados em técnicas de mapeamento e representações espaciais. Nesse sentido, propomos aqui uma série de procedimentos para compreender a doença no espaço, primeiramente com a exploração e descrição dos dados, a análise espacial e a síntese por meio da modelização gráfica, partindo em seguida para a comunicação cartográfica. Como efeito, esperamos que esse caminho teórico e metodológico possa balizar a criação de uma imagem de mundo capaz de responder a demandas mais urgentes postas pela pandemia, ao mesmo tempo criar reflexões sobre como a produção do espaço atual cria vulnerabilidades nesta globalização perversa.
Keywords: Geographic reasoning; Exploratory analysis; Modeling; Visualization; Covid-19; Raciocínio geográfico; Análise exploratória; Modelagem; Visualização; Covid-19